Development of an Antibacterial Dentin Adhesive - Lopes, Stephanie R. [UNESP]; Matuda, Amanda G. N. [UNESP]; Campos, Raquel P. [UNESP]; Mafetano, Ana Paula V. P. [UNESP]; Barnabe, Ana Helena M. [UNESP]; Chagas, Gabriela S. [UNESP]; Barcellos, Daphne C.; Niu, Li-Na; Tay, Franklin R.; Pucci, Cesar R. [UNESP] (MDPI, 2022)
Nisin is a peptide that possesses potent antibacterial properties. This study evaluated the antibacterial activity of a nisin-doped adhesive against Streptococcus mutans, as well as its degree of conversion and microtensile bond strength (µTBS) to dentin. Nisin was added to the adhesive Adper Single Bond 2 (3M ESPE), resulting in four groups: Control Group (Single Bond 2); Group 1% (1 wt% nisin-incorporated), Group 3% (3 wt% nisin-incorporated) and Group 5% (5 wt% nisin-incorporated). Antibacterial activity against S. mutans was evaluated using colony-forming unit counts (CFU). The degree of conversion was tested using FTIR. Forty human teeth were restored for µTBS evaluation. Data were statistically analyzed with ANOVA and Tukey tests at α = 0.05. The nisin-doped adhesives, for all concentrations, exhibited a significant inhibition of the growth of S. mutans (p < 0.05); Incorporation of 5% and 3% nisin decreased the degree of conversion of the adhesive (p < 0.05). The µTBS (in MPa): Control Group—38.3 ± 2.3A, Group 1%—35.6 ± 2.1A, Group 3%—27.1 ± 1.6B and Group 5%—22.3 ± 1.0C. Nisin-doped adhesives exerted a bactericidal effect on S. mutans. The µTBS and degree of conversion of adhesive were not affected after incorporation of 1% nisin.
Keywords: antibacterial activity; dentin; etch-and-rinse adhesive; nisin